An Analysis of the Effects of the English Language and Literature on Students' Language Ability from a Multidimensional Environment. (13th September 2022) - Chen, Weifang
Abstract : One of the most crucial components of a student's language proficiency is basic language proficiency, which is also its fundamental component. The development of students' language skills is greatly aided by ELL (English Language and Literature). It can not only foster the growth of students' language thinking but also widen their perspectives and enhance their capacity for language comprehension. In this essay, the rules of English are examined from the multifaceted ELL viewpoint. This study extracts personality characteristic data from practical texts and incorporates it into a modelling process of students' knowledge changes based on DM- (data mining-) related technology and multidisciplinary expertise. According to the t -test results, ELL, which incorporates communicative competence, has started to take on a role in education and is helping students' language skills. The performance gains are 3.95, 4.21, and 3.66, when the number of computing nodes is increased to 10, 20, and 30 times that of the original nodes, and the linear expansion indices are 0.914, 0.928, and 0.93. This proves that the Hadoop+Hive-based data cleaning tool has excellent linear scalability.